Advances in communication of design : proceedings of the AHFE 2017 International Conference on Human Factors in Communication of Design, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on Human Factors in Communication of Design, July 17-21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. (2018) - Unknown
No abstract available